Macroprudential policy and the sovereign-bank nexus in the euro area - Nikolay Hristov; Oliver Hülsewig; Benedikt Kolb (Deutsche Bundesbank, 2021)
We explore how changes in capital-based macroprudential regulation affect theexposure of national banking sectors to domestic government debt in the euro area,thus strengthening or weakening the sovereign-bank nexus. To do so, we construct ameasure of macroprudential policy based on theMacroprudential Policy EvaluationDatabaseand estimate responses to theunsystematiccomponent of macroprudentialpolicy in panel vector autoregressive models for euro area 'core" and 'periphery"countries. Our main finding suggests that an unsystematic capital-based macro-prudential policy tightening increases banks' exposure to domestic sovereign bondsin the periphery countries and so deepens the sovereign-bank nexus. By contrast,banks in the core countries expand their loan portfolios rather than adjusting theirdomestic sovereign bond holdings in response to the shock. We show that this re-sult can be tied to the theoretical literature and investigate several transmissionchannels. Our results are highly robust to changes in the econometric setup and themacroprudential indicator used.
Keywords: C33; G21; G28; H3; 330; macroprudential policy; euro area; sovereign-bank nexus; panel vector autore-gressive model